INNOVATIVE EDUCATION: THE ROLE OF FORESTALL STRATEGY AND INTEGRATION - Roman G. Strongin; Evgeny V. Chuprunov (Высшее образование в России)
The experience in elaborating the forestall university strategy and the assessment of its role in the development of innovative educational programs is under consideration. It is outlined that the substantial amount of resources and effort needed for implementation of such innovative programs require thorough selection of priorities in development accepted by the university community. The authors single outthe important role of project management in integration with university partners.